Restructuring of the epiphytic microbiome and recruitment of algicidal bacteria by Vallisneria natans for the suppression of Microcystis - Gao, Yunni; Wei, Ying; Zeng, Dahai; Zhang, Jingxiao; Dong, Jing; Gao, Xiaofei; Yuan, Huatao; Li, Xuejun; Qiu, Dongru; Burford, Michele (Frontiers in Plant Science, 2026)
The effective suppression of cyanobacteria by submerged macrophytes is a key mechanism underlying the successful restoration of aquatic vegetation in some eutrophic water bodies. However, the responses and functional roles of epiphytic microorganisms in this process remained largely unclear, limiting a clear understanding of how macrophytes inhibit cyanobacterial growth. In this study we investigated the temporal dynamics of the epiphytic microbiome on Vallisneria natans before, during and after exposure to toxic cyanobacterium Microcystis, corresponding to three distinct physiological stages of the plant: pre-stress, stress, and recovery. It was observed that the diversity of epiphytic bacteria and eukaryotic algae increased during the stress stage, while that of other eukaryotes, particularly fungi and protozoa, decreased. The complexity and stability of the epiphytic microbiome were enhanced, with bacteria emerging as central hubs in the co-occurrence network in response to Microcystis stress. More importantly, a selective enrichment and recruitment of potential algicidal bacteria, particularly Streptomyces, Pseudomonas and Chryseobacterium, occurred on macrophyte surfaces during the stress phase. Their abundance peaked under Microcystis stress and returned to baseline levels during the plant recovery phase. Our findings demonstrate that V. natans did not function alone, but rather actively recruited and sustained a beneficial microbiome to enhance its suppressive effects on Microcystis. This study revealed a previously neglected macrophyte-epiphytic microbiome synergy, providing novel mechanistic insights into how submerged vegetation effectively suppresses harmful cyanobacteria.